Effective pain management strategies for common pediatric conditions - Alzamzami, Abdulghani Abdulaziz; Alqahtani, Mona Ali; Kamal, Esraa Ebraheem; Alfehaid, Nouf Adel; Alali, Zainab Taleb; Binsalman, Sara Abdullah; Alajlani, Shouq Ibrahim; Asire, Rakan Nasser; Natto, Leen Hani; Aloqbi, Hanan Saleh; Batouk, Mohammad Abdlnasir (International Journal Of Community Medicine And Public Health, 2023)
Pain management in neonates, infants, and children is a complex and challenging aspect of healthcare, with a high prevalence of undertreatment. Efforts have been made to improve pain assessment and implement effective interventions. Pharmacological approaches include non-opioid analgesics, opioids, and adjuvant analgesics, while non-pharmacological interventions involve physical techniques and cognitive behavioral strategies. Pediatric pain management requires considering developmental stages, individual variability, and emotional factors. Accurate pain assessment, weight-based dosing, and involving parents are crucial. Minimizing procedural pain and addressing psychosocial aspects contribute to better outcomes. Comprehensive pain management is necessary to prevent long-term consequences and enhance recovery. However, there is a persistent gap between evidence-based guidelines and clinical practice, indicating the need for further education and training. Implementation of pain management protocols and multidisciplinary approaches involving healthcare providers, psychologists, physical therapists, and educators are essential. By adopting these strategies, healthcare providers can improve the quality of life for pediatric patients, reduce the burden on the healthcare system, and mitigate the long-term impact of untreated pain.